Nahwu and Shorof Analyzing on Fi’il Majhul in Surah Yasin - Muhtadin, Imam (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2017)
The researcher discussed about fi’il majhul because it was necessary to understand some of  Arabic language, and because fi’il majhul is different with fi’il ma’lum, and many beginners feel difficult in differentiating between fi’il majhul and fi’il ma’lum. The researcher choose surrat Yassin because surah Yasin is the heart of Qur’an. . The number of fi’il majhul in Surah Yasin is fourteen (14) verses, that be found is twelve (12) verses. The most fi’il majhul in Surah Yasin consists of fi’il stulatsi mujarrod, with 8 verbs. And others consist of fi’il tsulatsi mazid bi harfin with six (6) verbs. The researcher does not bounded fi’il tsulatsi mazid biharfain or tsalatsah or fi’il ruba’i in this surah. The number of fi’il majhul in Surat Yassin consists of bina’ shahih with nine (9) verbs.  bina’  ajwaf wawi with tree (3) verbs,  one verb from bina’ naqis lam at 54th verse, one verb from  bina’ mitsal wawi at 63rd verse, and the researcher does not find another building in this surah.